2021
DOI: 10.1002/ajmg.a.62064
|View full text |Cite
|
Sign up to set email alerts
|

Expansion of NEUROD2 phenotypes to include developmental delay without seizures

Abstract: De novo heterozygous variants in the brain‐specific transcription factor Neuronal Differentiation Factor 2 (NEUROD2) have been recently associated with early‐onset epileptic encephalopathy and developmental delay. Here, we report an adolescent with developmental delay without seizures who was found to have a novel de novo heterozygous NEUROD2 missense variant, p.(Leu163Pro). Functional testing using an in vivo assay of neuronal differentiation in Xenopus laevis tadpoles demonstrated that the patient variant of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Approaches such as ours that focus on children with undiagnosed diseases and couple NGS with laboratory assessments of gene and variant function are adding to the genetic lexicon, thereby improving the clinical diagnostic utility of NGS. While the rate of novel gene discovery in our Diagnosed cohort was 8%, it is worth noting that 56% of Diagnosed patients contributed some novel element to the body of rare disease knowledge, whether through novel variants of known genes, novel modes of inheritance for a condition, or expansion of a given condition's phenotype (AbuBakr et al, 2020; Amabile et al, 2020; Elfar et al, 2019; Kiraly‐Borri et al, 2019; Landim‐Vieira et al, 2019; Marquez et al, 2020; Mis et al, 2020; Mis et al, 2021; Najari Beidokhti et al, 2021; Sega et al, 2019). In addition, the patient‐centered approach of investigating molecular mechanisms underlying a rare disease can shed light on not just that specific condition, but can potentially reveal unexpected insights into normal biology or even into other diseases (Del Viso et al, 2016; Griffin et al, 2018; Kulkarni et al, 2018; Kulkarni & Khokha, 2018; Sempou et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Approaches such as ours that focus on children with undiagnosed diseases and couple NGS with laboratory assessments of gene and variant function are adding to the genetic lexicon, thereby improving the clinical diagnostic utility of NGS. While the rate of novel gene discovery in our Diagnosed cohort was 8%, it is worth noting that 56% of Diagnosed patients contributed some novel element to the body of rare disease knowledge, whether through novel variants of known genes, novel modes of inheritance for a condition, or expansion of a given condition's phenotype (AbuBakr et al, 2020; Amabile et al, 2020; Elfar et al, 2019; Kiraly‐Borri et al, 2019; Landim‐Vieira et al, 2019; Marquez et al, 2020; Mis et al, 2020; Mis et al, 2021; Najari Beidokhti et al, 2021; Sega et al, 2019). In addition, the patient‐centered approach of investigating molecular mechanisms underlying a rare disease can shed light on not just that specific condition, but can potentially reveal unexpected insights into normal biology or even into other diseases (Del Viso et al, 2016; Griffin et al, 2018; Kulkarni et al, 2018; Kulkarni & Khokha, 2018; Sempou et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…NeuroD2 has recently attracted attention because 2 recent studies identified de novo mutations in the DNA binding domain of NeuroD2 associated with early infantile epileptic encephalopathy in 2 children 2 and with neurodevelopmental delay in 1 child. 3 The first study confirmed the causative role of NeuroD2 mutation for the induction of epilepsy by using X. laevis tadpoles. CRISPR/Cas9 knockdown to mimic loss-of-function mutations led to seizures in tadpoles.…”
Section: Commentarymentioning
confidence: 93%
“…NeuroD2 sequence for human and X. laevis L and S proteins and X. laevis NeuroD2.S mRNA were obtained from NCBI and imported into SnapGene v5.2.4. Protein sequences were aligned in SnapGene using MUSCLE alignments and the bHLH, NLS domains and human DEE-causing variants annotated from the human sequence and data in previously published studies (SEGA et al 2019;MIS et al 2021). Using the InDelphi (SHEN et al 2018) online predicJon tool, 60 bp up-and downstream of the target Cas9 site in X. laevis NeuroD2.S were entered in "single mode" using mESC cell type, for each sgRNA.…”
Section: Methodsmentioning
confidence: 99%